(untitled) (Trinity Journal of Management, IT & Media (TJMITM), 2022)
In recent years, the growing insistence on better food quality & quantity has increased the need for agribusiness and stabilization. The Internet of Things (IoT) is the future lying ahead which is impacting everyone’s lives by showing intelligence. Research organizations and establishments of higher learning are perpetually operating to create solutions and products supported by IoT. The Internet of Things (IoT) is a technology that guarantees out-of-the-box solutions for contemporary agriculture. New Smart Farming innovations are being produced using IoT every day and are slowly but firmly changing the nature of traditional farming methods, not only by making them more efficient but also by reducing farmers’ prices. The goal is to unfold technology that can send alerts to farmers via various platforms. Farmers will gain from these products as they shall provide them with real-time data from their farms (temperature, soil moisture, humidity, etc), which allows them to take the mandatory steps to increase crop yields while preserving several resources like water, and fertilizer.